Strategi Modelling the Way: Upaya Meningkatkan Aktivitas dan Kemampuan Siswa dalam Melakukan Salat Wajib di SD Negeri Tancep 1 Ngawen - Satiman (Jurnal Pendidikan Madrasah, 2021)
This study aims to describe the increase in activities and ability to perform compulsory prayers through modelling the way strategy in grade V students of SD Negeri Tancep 1 Ngawen Semester 2 of 2016/2017. This research uses the Action research method. Data is collected through observations, interviews, and tests or assignments, while data analysis is done with interactive models. The results showed that the implementation of Modelling the Way strategy can improve the activities and ability to perform compulsory prayers in students. Learning activity from cycle I to cycle II increased in the aspect of reading the prayer pillars increased by 21.8% from the good category to excellent; the aspect of reading the prayer requirement increased by 14.8% from the good category to excellent; aspects of reading things that cancel prayers increased by 15.7% from the good category to very good; and aspects of prayer practice increased by 18.3% from the good category to excellent. Student learning outcomes from the initial condition to cycle II also experienced a significant increase from 7 students (30%) 23 students (100%) category. There was an increase of 16 students (70%) and the average grade from 60.2 to 85.0 increased by 24.8. Modelling the Way strategy can be applied to the learning process in the classroom.